GIL VALDO JOSÉ DA SILVA (1954-2023) - Donate, Paulo Marcos (Orbital: The Electronic Journal of Chemistry, 2023)
Gil Valdo José da Silva, from Guaimbê, São Paulo, rose above the constraints of his small-town upbringing. He moved to São Paulo in 1970 and graduated from the Antárctica Technical School with a degree in Industrial Chemistry. Initially employed by General Motors do Brasil, his zeal for knowledge drove him to pass the entrance exam at the University of S. Paulo’s Chemistry Institute (IQ-USP) in 1975. Balancing studies and work, he taught chemistry in schools and developed a passion for teaching. Gil Valdo graduated in 1980 and went on to undertake doctoral studies in organic synthesis of natural goods. He was interested in research, particularly chemical synthesis and Nuclear Magnetic Resonance (NMR) techniques. His accomplishments went beyond the classroom; he became a licensed pilot, a Dive Master, and a lover of languages, culinary arts, and winemaking. Gil Valdo retired in December 2021, after more than 30 years at FFCLRP-USP, to pursue his passions more freely. He died on July 21, 2023, as a result of a heart attack. He was survived by a loving family and a legacy of intellectual, scientific, and cultural achievements. Gil Valdo José da Silva will be remembered for his serenity, dedication, and the diverse interests that enriched his life and the lives of those who were lucky enough to know him.